Longitudinal changes in attention bias to infant crying in primiparous mothers - Hiraoka, Daiki; Makita, Kai; Sakakibara, Nobuko; Morioka, Shigemi; Orisaka, Makoto; Yoshida, Yoshio; Tomoda, Akemi (Frontiers in Behavioral Neuroscience, 2023)
Infant stimuli attract caregiver attention and motivate parenting behavior. Studies have confirmed the existence of attentional bias toward infant face stimuli; however, relatively little is known about whether attentional bias exists for infant cry stimuli, which are as important as faces in child-rearing situations. Furthermore, scarce longitudinal evidence exists on how attentional bias toward infant crying changes through the postpartum period. In the present study, we conducted an experiment to assess bias toward infant crying at two postpartum time points: at Time 1 (Mean = 75.24 days), 45 first-time mothers participated and at Time 2 (Mean = 274.33 days), 30 mothers participated. At both time points, the mothers participated in a Stroop task with infant crying and white noise as the stimuli. They were instructed to answer the color out loud as quickly and accurately as possible, while ignoring the sound. Four types of audio stimuli were used in this task (the cry of the mother’s own infant, the cry of an unfamiliar infant, white noise matched to the cry of the mother’s own infant, and white noise matched to the cry of an unfamiliar infant), one of which was presented randomly before each trial. Response time and the correct response rate for each condition were the dependent variables. For response time, the main effect of familiarity was significant, with longer response times when the participant’s infant’s cry was presented. In addition, response times were lower at Time 2 than at Time 1 in some conditions in which crying was presented. The results suggest that mothers may be less disturbed by infant crying as they gain more experience. Elucidating the characteristics of postpartum mothers’ changes in cognitive performance related to infants’ cries would be useful in fundamental and applied research to understand the process of parents’ adaptation to parenting.